2019
DOI: 10.1016/j.smrv.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia as a predictor of mental disorders: A systematic review and meta-analysis

Abstract: Previous research has identified insomnia as a predictor for the onset of depression. The aim of this meta-analysis is to investigate whether insomnia also predicts the onset of other mental disorders. Longitudinal studies were eligible for inclusion if they investigated insomnia at baseline (including nighttime-and daytime-symptoms) as a predictor of the later onset of psychopathology within a follow-up time-frame of at least 12 months. Thirteen primary studies were included. The results suggest that insomnia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
493
1
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 774 publications
(537 citation statements)
references
References 50 publications
31
493
1
12
Order By: Relevance
“…The criteria for entering the study included complete consent for participating in the study, the participants had to be between 18 and 60 years old, the participants had to have at least nine years of education, and the participants must not be suffering from chronic physical illnesses such as diabetes, cardiovascular diseases, pulmonary diseases, and diseases related to thyroid glands (1)(2)(3)(4). The criteria for eliminating the participants from the study included suffering from other sleep disorders, being under simultaneous treatment with other therapies, suffering from chronic mental disorders, particularly personality disorders, and being addicted to any illicit drugs (1)(2)(3)(4). In order to abide by the ethical rules of research, the participants were informed that they can exit the study in case they have any problems with the participation.…”
Section: Sample and Sampling Methodsmentioning
confidence: 99%
“…The criteria for entering the study included complete consent for participating in the study, the participants had to be between 18 and 60 years old, the participants had to have at least nine years of education, and the participants must not be suffering from chronic physical illnesses such as diabetes, cardiovascular diseases, pulmonary diseases, and diseases related to thyroid glands (1)(2)(3)(4). The criteria for eliminating the participants from the study included suffering from other sleep disorders, being under simultaneous treatment with other therapies, suffering from chronic mental disorders, particularly personality disorders, and being addicted to any illicit drugs (1)(2)(3)(4). In order to abide by the ethical rules of research, the participants were informed that they can exit the study in case they have any problems with the participation.…”
Section: Sample and Sampling Methodsmentioning
confidence: 99%
“…Insomnia is a costly condition. At present, it has been shown, on a meta‐analytic level, to convey increased risks of cardiovascular diseases (Li, Zhang, Hou, & Tang, ; Sofi et al, ; Spiegelhalder, Scholtes, & Riemann, ), obesity and development of diabetes (Anothaisintawee, Reutrakul, Van Cauter, & Thakkinstian, ; Chan, Levsen, & McCrae, ), depression (Baglioni et al, ; Hertenstein et al, ), anxiety (Hertenstein et al, ) and suicide (Norra & Richter, ; Pigeon, Pinquart, & Conner, ). Wickwire () reported that untreated insomnia is associated with increased all‐causes healthcare utilization based on a randomly selected and nationally representative sample from the USA.…”
Section: An Introduction To Insomnia Disorder In Europe: Epidemiologymentioning
confidence: 99%
“…Insomnia affects over 20% of the general population and up to 5-10% use hypnotics [13], with a tendency in recent years to an increase in some countries including the USA and an increase in benzodiazepine-related deaths [14]. Associations have been reported between insomnia and depression, anxiety, hypertension, diabetes and cardiovascular disorders [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%